2008
DOI: 10.7150/ijbs.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Bmp13 Enigma: Redundant Morphogen or Crucial Regulator?

Abstract: Bone morphogenetic proteins are a diverse group of morphogens with influences not only on bone tissue, as the nomenclature suggests, but on multiple tissues in the body and often at crucial and influential periods in development.The purpose of this review is to identify and discuss current knowledge of one vertebrate BMP, Bone Morphogenetic Protein 13 (BMP13), from a variety of research fields, in order to clarify BMP13's functional contribution to developing and maintaining healthy tissues, and to identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 93 publications
1
28
0
Order By: Relevance
“…We did not find decreased Bmp4 expression after inhibition of NRas by siRNA in our dataset, but we did find that the expression of Gdf6, also known as Bmp13, significantly increased in ST88-14 cells (DS-4) but decreased in siNRas-treated sample (DS-2). GDF6 is believed to bind the same type I and II receptors as BMP2, which results in phosphorylation/activation of SMAD1/5/8 (43). This mechanism may explain the phosphorylation/activation of SMAD1/5/8 that we observed in the regulation of SMAD1/ 5/8 by the NRAS pathway.…”
Section: Discussionsupporting
confidence: 63%
“…We did not find decreased Bmp4 expression after inhibition of NRas by siRNA in our dataset, but we did find that the expression of Gdf6, also known as Bmp13, significantly increased in ST88-14 cells (DS-4) but decreased in siNRas-treated sample (DS-2). GDF6 is believed to bind the same type I and II receptors as BMP2, which results in phosphorylation/activation of SMAD1/5/8 (43). This mechanism may explain the phosphorylation/activation of SMAD1/5/8 that we observed in the regulation of SMAD1/ 5/8 by the NRAS pathway.…”
Section: Discussionsupporting
confidence: 63%
“…These results are not surprising, as members of the larger family of BMPs exhibit overlapping functions and sites of expression36. Speculation regarding the functional roles of individual GDF family members based on knockout mouse models should be made with caution, however, for the high degree of amino acid homology (80-86%) seen in the C-terminal active domain of these proteins likely makes it possible for one member to compensate for another36. Based on our gene expression results, it does not appear that GDFs 5 or 7 are overcompensating in the absence of GDF6 in male or female tendons at either age or tendon location.…”
Section: Discussionmentioning
confidence: 88%
“…No data have been published comparing the gene expression levels of individual GDF family members between tendons from different anatomical locations, but previous studies in GDF5 and GDF7 deficient mice demonstrated more pronounced phenotypes in the Achilles tendon versus the tail, whereas our results suggest a more prominent effect of GDF6 deficiency on the tail. These results are not surprising, as members of the larger family of BMPs exhibit overlapping functions and sites of expression36. Speculation regarding the functional roles of individual GDF family members based on knockout mouse models should be made with caution, however, for the high degree of amino acid homology (80-86%) seen in the C-terminal active domain of these proteins likely makes it possible for one member to compensate for another36.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-7, BMP-2 and BMP-14 have also been tested in animal models of IVD regeneration 6-8. BMP13 (also known as growth & differentiation factor-6, GDF6 and cartilage derived morphogenetic protein-2, CDMP2) has an important role in early embryonic and ocular development 9 and more recently was shown to play a role in spinal column development 10. Congenital gene mutations caused spinal vertebral fusions, perhaps revealing a crucial role for BMP13 in disc tissues which could be applied to adult tissue maintenance and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital gene mutations caused spinal vertebral fusions, perhaps revealing a crucial role for BMP13 in disc tissues which could be applied to adult tissue maintenance and repair. In vitro studies suggest BMP13 promotes the expression of chondrogenic marker genes in a variety of cell types 9,11,12 including bovine intervertebral disc 13,14. Indeed BMP13 was recently shown to inhibit expression of both early and late markers of osteogenic differentiation in vitro 15.…”
Section: Introductionmentioning
confidence: 99%